Mendudukkan Lingkup Pemantauan Dan Evaluasi Peraturan Daerah Oleh Dewan Perwakilan Daerah - Triya Indra Rahmawan (SAPIENTIA ET VIRTUS, 2018)
Upon the enactment of Law No 2 in 2018, the Regional Representative Council has been given a new authority and task to monitor and evaluate the Local Regulations. The establishment of the new authority and task has provided a challenge for the Regional Representative Council in determining the scope of monitoring and evaluation. Overlap of functions might occur because the central government is also responsible for supervising the Local Regulations. Therefore, the Regional Representative Council should be able to spot the differences in the Local Regulations supervised by the legislative or executive councils. To avoid overlapping authorities, the monitoring and evaluation scope should be focused on formulating problems that are faced by the local government in planning, preparing, and implementing the Local Regulations. These results will, thus, be established in a form of a policy recommendation for preparing materials contained in a local autonomy law.